PENGEMBANGAN MEDIA POP-UP BOOK DWIBAHASA PADA MATERI DONGENG AYAM JAGO BARU TERHADAP KETERAMPILAN BERBICARA SISWA - Anisa Zahara Darmawati; Rina Yuliana; Sundawati Tisnasari (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2021)
This research aimed to determine the steps for the development and feasibility of bilingual Pop-up Book learning media for fairy tale material. The research method was Research and Development (R&D) method, referring to Borg and Gall model adapted by Sugiyono. This model consisted of 10 stages (1) potentials and problems (2) data collection (3) product design (4) design validation (5) design revision (6) small group product trials (7) design revision (8) testing large group products (9) final stage product revision (10) mass production. However, in this study it was only limited to 6 stages. Expert validation was carried out by material experts, linguists, and media experts. The subjects of this research were grade III students at SDN Unyur, totaling 10 students for limited product trials. The results showed that the percentage of material expert validation was 79% with feasible category; the linguist validation score was 79% with feasible category; the media expert validation score was 89% with very feasible category; and the assessment score in limited trialswas 82% with very good category. Based on the research results, it was concluded that bilingual pop-up book media was suitable for learning to read fairy tales.